2009
DOI: 10.1029/2008jd011618
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the X‐ray emission from rocket‐triggered lightning as measured by the Thunderstorm Energetic Radiation Array (TERA)

Abstract: [1] The Thunderstorm Energetic Radiation Array (TERA) is located at the University of Florida, Florida Tech International Center for Lightning Research and Testing (ICLRT) at Camp Blanding, Florida. The array includes forty-five 7.6-cm-diameter NaI/photomultiplier tube detectors enclosed in 24 separate aluminum boxes that shield the detectors from light, moisture, and RF noise. The array covers the $1 km 2 ICLRT facility, centered on the rocket launch tower, used to trigger lightning. From 2005 to 2007, TERA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
165
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(170 citation statements)
references
References 44 publications
2
165
1
Order By: Relevance
“…The Monte Carlo code used in this work was developed at Florida Tech in 2002 by J. R. Dwyer [ Dwyer , 2003, 2004, 2005, 2007, 2008, 2009, 2010; Coleman and Dwyer , 2006; Saleh et al , 2009; Dwyer et al , 2009; Dwyer and Babich , 2011]. This Monte Carlo simulation of relativistic runaway electron avalanches is capable of modeling the development and propagation of runaway electron avalanches in any gaseous medium for both spatially and time‐varying electric and magnetic fields.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Monte Carlo code used in this work was developed at Florida Tech in 2002 by J. R. Dwyer [ Dwyer , 2003, 2004, 2005, 2007, 2008, 2009, 2010; Coleman and Dwyer , 2006; Saleh et al , 2009; Dwyer et al , 2009; Dwyer and Babich , 2011]. This Monte Carlo simulation of relativistic runaway electron avalanches is capable of modeling the development and propagation of runaway electron avalanches in any gaseous medium for both spatially and time‐varying electric and magnetic fields.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…Indeed, X‐rays are now routinely measured from natural cloud‐to‐ground and rocket‐and‐wire‐triggered lightning. In a series of experiments beginning in 2002 at the University of Florida/Florida Tech International Center for Lightning Research and Testing (ICLRT) at Camp Blanding, FL, it was found that lightning produces significant X‐ray emission up to about an MeV during the stepped‐leader phase of natural lightning and during the dart‐leader phase of natural and rocket‐and‐wire‐triggered lightning, with the most intense emission often detected immediately before the return stroke during the attachment process [ Dwyer et al , 2004b, 2005; Howard et al , 2008; Saleh et al , 2009; Howard et al , 2010]. The X‐rays are usually observed to arrive in short (<1 μ s) bursts in coincidence with the step formation of the stepped leaders and dart‐stepped leaders.…”
Section: Cold Runaway Electron Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray emissions have been measured successfully over a span of about ten years from triggered lightning and natural lightning in Florida at distances up to about a kilometre from the lightning channel [16][17][18][19]. According to experiments carried out in Gainesville, Florida, the maximum source height of X-rays corresponding to first-stroke stepped leaders and dart-stepped leaders of natural lightning are 800 m and 3.6 km respectively [19].…”
Section: Discussionmentioning
confidence: 99%
“…The detector used is similar to the detector described in more detail in [18] by Saleh et al Two fibre-optic links (of type Terahertz Technologies V-250, with a bandwidth of 10 MHz, and input voltage peak-to-peak threshold of 1 V) carried the detector signal to a transient recorder inside the EMC cabinet. The X-ray detection system (the detectors and fibre-optic transmitters) was powered by two 12 V batteries also housed inside the same aluminium box as the detectors.…”
Section: Methodsmentioning
confidence: 99%